Persepsi Jemaah Terhadap Bimbingan Manasik Umrah di Biro Saibah Mulia Mandiri Semarang Pada Tahun 2025 - Butsainah, Innas Salma; Anas, Ahmad; Rozaq, Abdul; Hilmi, Mustofa; Kasmuri, Kasmuri; Darissurayya, Vina (Jayapangus Press, 2025)
The implementation of umrah manasik guidance is the most important aspect in preparing the congregation, especially for beginners and the elderly so that they are able to understand the procedures for worship before leaving for the holy land. This study aims to describe the experiences and perceptions of the congregation towards the umrah manasik service provided by the Saibah Mulia Mandiri Semarang Bureau. The approach used is descriptive qualitative with data collection techniques through interviews with ten informants who are umrah pilgrims and one bureau staff. In analyzing, the researcher refers to the five dimensions of SERVQUAL, namely tangible, reliability, responsiveness, assurance, and empathy. The results of the study indicate that the service is good with several suggestions for improvement in the form of adding animated media and practicing the pillars of tawaf and sa'i worship for the congregation. Apart from that, this study can provide practical contributions in improving the quality of service at the Umrah Pilgrimage Travel Organizer (PPIU).